Molecular characterization of some isolates of rabbit viral hemorrhagic disease (VHD) in Egypt from 2014 to 2019 (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Rabbit viral hemorrhagic disease (VHD) is a transmittable and lethal viral illness of rabbits. In this study, genetic identification and genetic analysis of the rabbit hemorrhagic disease virus (RHDV) was made in three governorates in Egypt from 2014 to 2019.  Materials and Methods: Livers from 18 freshly dead rabbits, which was guessed to be VHD epidemics in Egypt (Giza, Menofia, and Fayoum governorates) from 2014 to 2019, were examined for RHDV. The examination was based on the hemagglutination assay (HA) test against different mammalian (human O-type and sheep) and avian (chicken and pigeon) erythrocytes, reverse transcriptase-polymerase chain reaction (RT-PCR), and sequencing of the segment of VP60.  Results: 33% of the examined samples’ virus titers were 5 log2 to 8 log2 hemagglutination of human O-type erythrocytes when compared to 28%, 11%, and 28% of sheep, chicken, and pigeon erythrocytes, respectively. Four RHDV isolates out of eight RT-PCR positives were sequenced and phylogenetically analyzed. Sequenced isolates were designed and submitted to GenBank with accession numbers MN904506, MN904507, MN904508, and MN904509. These four RHDV isolates were related to classic G3 (GI.1d/RHDV). Twelve amino acid differences were detected between the vaccine strain sequence (Giza-2006) and RHDV isolates. Amino acid differences at 416, 423, and 476 positions seem interesting as they changed polarity that could change the protein structure and affect host interaction.  Conclusions: There is antigenic variation between circulating RHVD strains and the vaccinal strain. This may be the leading cause of vaccination failure and may increase the need to check out the vaccination program against RHVD.J. Adv. Vet. Anim. Res., 8(3): 396-403, September 2021http://doi.org/10.5455/javar.2021.h528